2020
DOI: 10.1097/scs.0000000000007024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Nasal Septal Anatomy and Physiology Following Le Fort I Osteotomy for Orthognathic Surgery

Abstract: Orthognathic surgery utilizing a Le Fort I osteotomy is performed by oral and maxillofacial surgeons to correct midface and dental occlusal abnormalities. However, the potential sequelae on sinonasal function have had minimal discussion in the literature. The objective of this study was to assess the impact on nasal septum anatomy and physiology following Le Fort I osteotomy for maxillary repositioning surgery. Thirty patients who previously underwent elective orthognathic surgery with Le Fort I osteotomy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In previous studies, it was found that surgery to correct midfacial dysplasia may affect the nasal septum and nasal airway. Traditional Le Fort osteotomy can increase the nasal airway volume and reduce the total nasal resistance, 30 but is associated with a risk of nasal septum perforation 31 . Le Fort I-DO can also increase the nasal also airway volume 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was found that surgery to correct midfacial dysplasia may affect the nasal septum and nasal airway. Traditional Le Fort osteotomy can increase the nasal airway volume and reduce the total nasal resistance, 30 but is associated with a risk of nasal septum perforation 31 . Le Fort I-DO can also increase the nasal also airway volume 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Le Fort osteotomy can increase the nasal airway volume and reduce the total nasal resistance, 30 but is associated with a risk of nasal septum perforation. 31 Le Fort I-DO can also increase the nasal also airway volume. 32 These studies suggest that surgery to correct midfacial dysplasia can play a role in improving nasal airway stenosis, which is similar to our findings.…”
Section: Discussionmentioning
confidence: 99%